2017
DOI: 10.1080/19336896.2017.1314426
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric measurement of the cellular propagation of TDP-43 aggregation

Abstract: ABSTRACT. Amyotrophic lateral sclerosis is a devastating neuromuscular degenerative disease characterized by a focal onset of motor neuron loss, followed by contiguous outward spreading of pathology including TAR DNA-binding protein of 43 kDa (TDP-43) aggregates. Previous work suggests that TDP-43 can move between cells. Here we used a novel flow cytometry technique (FloIT) to analyze TDP-43 inclusions and propagation. When cells were transfected to express either mutant G294A TDP-43 fused to GFP or wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
(39 reference statements)
2
26
0
Order By: Relevance
“…We used a recently developed flow cytometry method, which counts fluorescent particles in cell lysates and normalizes this count against the number of separately enumerated nuclei (FloIT; [ 25 , 36 , 37 ]) to quantify the numbers of TDP-43 M337V -GFP inclusions in differently treated N2a cells. The results indicated that (i) in unstressed cells, overexpression of CLU or mCherry had no significant effect on the numbers of TDP-43 M337V -GFP inclusions, (ii) the numbers of inclusions were increased in cells treated with either thapsigargin (Tg) alone (to induce ER stress), or with Tg and MG132 (the latter to also inhibit the proteasome), and (iii) overexpression of CLU, but not mCherry, reduced the numbers of TDP-43 M337V -GFP inclusions in ER-stressed cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used a recently developed flow cytometry method, which counts fluorescent particles in cell lysates and normalizes this count against the number of separately enumerated nuclei (FloIT; [ 25 , 36 , 37 ]) to quantify the numbers of TDP-43 M337V -GFP inclusions in differently treated N2a cells. The results indicated that (i) in unstressed cells, overexpression of CLU or mCherry had no significant effect on the numbers of TDP-43 M337V -GFP inclusions, (ii) the numbers of inclusions were increased in cells treated with either thapsigargin (Tg) alone (to induce ER stress), or with Tg and MG132 (the latter to also inhibit the proteasome), and (iii) overexpression of CLU, but not mCherry, reduced the numbers of TDP-43 M337V -GFP inclusions in ER-stressed cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, the intercellular transfer of TDP-43 has been demonstrated [21, 47, 57, 67]. However, whether this also occurs in vivo remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Significant recent interest in the field has focussed on the potential cell-to-cell transfer of TDP-43 and/or associated proteins, and the possibility that this might facilitate propagation of the disease process through the motor system. In vitro, the intercellular transfer of TDP-43 has been demonstrated [ 21 , 47 , 57 , 67 ]. However, whether this also occurs in vivo remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…In cell culture, “prion-like” seeding and propagation of aggregation have been observed for proteins that are heavily involved in neurodegenerative diseases, such as Parkinson’s, Huntington’s and ALS [ 6 , 7 , 8 ]. More specifically, researchers have observed this “prion-like” behavior in TDP-43 extracted from diseased brains of ALS and frontotemporal lobar dementia (FTLD) patients [ 9 , 10 , 11 ], as well as from overexpressed TDP-43 in co-culture [ 12 ] and in conditioned medium [ 13 ]. This propagation has been associated with cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%